Accessibility factors for totally blind users of Palestinian universities websites - Hassouna, Mohammed Saleh; Sahari, Noraidah; Ismail, Amirah (2015)
The World Wide Web (Web) is considered to be one of the sources of information and services.Universities use their webpages to communicate with stakeholders.Most of the related researchers have discovered significant faults with respect to accessibility of university websites, especially for blind users.In order to determine the totally blind requirements for designing websites, this study conducted a comprehensive literature review and based it on the Web Content Accessibility Guidelines, WCAG 2.0. The study revealed important factors in designing an accessible university webpage prototype. An online questionnaire was constructed to evaluate the accessibility of the prototype from blind users’ perspective.From the evaluation of 16 visually impaired participants, it was found that the prototype was highly accessible among the totally blind where the mean score was 4.19. A regression analysis test was also utilized to determine the relationship between the items of the questionnaire and the main principles of accessibility.The results showed that there were statistically significant differences between these items.In conclusion, the accessibility factors are indirectly validated, and could be used to develop an accessible university website for blind users.